Effect of Polyethylene Glycol on the Properties of γ-Al 2 O 3 Formation by Polyaluminum Chloride - 赵长伟 王孝年 何劲松 王园园 栾兆坤 (中国化学工程学报：英文版, 2012)
A polyaluminium chloride solution with high Al 13 content self-prepared was used as material for preparing the spherical γ-Al 2 O 3 by the sol-gel and oil-drop method. Polyethylene glycol with different molecular mass was used as surfactant to investigate the effect on property of γ-Al 2 O 3 . The physical property was characterized by 27 Al NMR （nuclear magnetic resonance） spectra, X-ray diffraction, FT-IR （Fourier transform infrared spectroscopy） and TG-DTA （thermogravimetric-differential thermal analysis）. The results showed that surface area, pore volume and pore size of γ-Al 2 O 3 all increased with the increase of polyethylene glycol molecular mass in the experimental research range, and polyethylene glycol 10000 was the most suitable pore forming additive. γ-Al 2 O 3 with surface area of 339 m 2 ·g 1 , pore volume of 0.59 cm 3 ·g 1 and pore diameter of 6.9 nm were obtained at 450 °C.